Motivations and achievements for mid-career change into farming occupation - Suwan, P.; Opatpatanakit, A. (International Journal of Agricultural Technology, 2015)
Withdrawal of people from rural agricultural sector to take up non-farm employment has been a common phenomenon statistically and visually. The present article, however, deals with an antithetical occurrence of people previously employed in non-farm occupation but now turning to work on farm. It is based on the first author’s research in qualitative approach for her dissertation writing. In-depth information was collected from 12 “recently turned farmers”. Apparently, there are both push and pull factors underlying individual’s motivations to make mid-career change namely the problems or limitations in previous job and the positive expectation about farming profession. Specifically, salary persons have to endure work-related stress like that from fixed working hours and schedule which allow them no freedom to spend time as they needed for themselves or family. Meanwhile, farming occupation is believed to allow one to his boss in terms of decision making and management of time, get closer with family for better relationship, realize food and income security, and live in a non-polluted environment. All these would give one and his family a sound psychological as well as physical health. Thus the most common farming system adopted has been organic agriculture including vegetable, rice, fruit tree, and livestock production. The 12 representatives of recently turned farmers indicated the most crucial factor for success in their new occupation was their ability to acquire good farming knowledge and so far they have achieved a better quality of life as manifested by the improvement in family health and economic conditions as well as their self-reliant capacity particularly from minimization of food and production input costs. To make farming occupation more appealing and successful for those newcomers into agricultural sector, it is recommended that knowledge exchange group be formed among the recently turned farmers and particularly relevant agricultural extension workers arrange activities for the exchange of knowledge, experience, and information about local resources like water for farm irrigation between the long time farmers and those new ones in a specific community area.